Effect of ropivacaine, mepivacaine or the combination of ropivacaine and mepivacaine for epidural anaesthesia on the postoperative recovery in patients undergoing caesarean section: a randomized, prospective, double-blind study - Muye Wang; Chen Liao; Xiaocui Li; Weiming Chen; Yujie Li; Wei Zhang; Shouping Wang (BMC Anesthesiology, 2024)
Abstract Background Anaesthetic methods and drugs with rapid onset, rapid recovery and better postoperative analgesia are more suitable for rapid recovery in obstetric anaesthesia. We formulated the following hypothesis: a combination of mepivacaine and ropivacaine could provide a longer analgesic effect and have more advantages in terms of rapid-recovery indicators. Methods A total of 180 pregnant women scheduled to undergo elective caesarean sections were randomly assigned to three surgical groups, which received 2% mepivacaine (Group M), 2% mepivacaine + 0.75% ropivacaine (Group MR) (Volume 1:1) or 0.75% ropivacaine (Group R) through an epidural catheter. The situation of postoperative analgesia and other indicators of rapid recovery were recorded. Results One hundred and fifty patients were included in the final analysis. Their demographic data were similar. The visual analogue scale (VAS) scores of Group MR and Group R were lower than Group M at 1 and 2 h after surgery both at rest and with movement (P < 0.05), and the time to first ambulation in Group MR (17.38 ± 2.06 h) and Group M (17.20 ± 2.09 h) was shorter than that in Group R (22.18 ± 1.74 h) (P < 0.05). Conclusion Application of 2% mepivacaine combined with 0.75% ropivacaine for epidural anaesthesia can provide longer postoperative analgesia and earlier ambulation, these effect may be more suitable than that of 2% mepivacaine or 0.75% ropivacaine alone for caesarean section. Trial registration This study was registered at Chinese Clinical Trial Registry (Registration number: ChiCTR 2300078288; date of registration: 04/12/2023).